2012
DOI: 10.1111/j.1540-5893.2012.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Ignorance in Bliss: Modeling Knowledge of Rights in Marriage and Cohabitation

Abstract: We live our lives against an extensive backdrop of legal rights and responsibilities, yet a growing number of studies indicates low levels of public legal literacy. In the context of opposite‐sex cohabitation and marriage law, this study employs new survey data from the United Kingdom to explore, in detail, how many and which people are ignorant of the law, and what are the nature and origins of erroneous beliefs. We find that people's beliefs about both cohabitation and marriage law are frequently wrong. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Whilst findings corroborated those of other related studies (e.g. Meager et al , 2002 , Kim 1999 ) as Pleasence and Balmer (2012) observed, the BSAS questions relied on a presumption that people had good knowledge of the spousal rights against which cohabitants’ rights were being compared, resulting in conflation between knowledge of spousal rights and knowledge of cohabiting rights. Thus, in their 2012 study on the same topic using respondents to the English and Welsh Civil and Social Justice Panel Survey (CSJPS), Pleasence and Balmer (2012) also developed a series of fact-based questions in relation to a hypothetical scenario but randomly varied the duration of the relationship (one month to 20 years – allowing formal modelling of time dependency in beliefs about accrual of rights) and its status (cohabiting or married).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Whilst findings corroborated those of other related studies (e.g. Meager et al , 2002 , Kim 1999 ) as Pleasence and Balmer (2012) observed, the BSAS questions relied on a presumption that people had good knowledge of the spousal rights against which cohabitants’ rights were being compared, resulting in conflation between knowledge of spousal rights and knowledge of cohabiting rights. Thus, in their 2012 study on the same topic using respondents to the English and Welsh Civil and Social Justice Panel Survey (CSJPS), Pleasence and Balmer (2012) also developed a series of fact-based questions in relation to a hypothetical scenario but randomly varied the duration of the relationship (one month to 20 years – allowing formal modelling of time dependency in beliefs about accrual of rights) and its status (cohabiting or married).…”
Section: Introductionsupporting
confidence: 83%
“…In respect of this latter group, although their answer appeared correct in relation to their dispute, it was not possible to deduce the basis of their knowledge, i.e. whether it stemmed from an understanding of the legislation, or whether it was based on a common sense position as found by Kim (1999), Meager et al , (2002), Barlow et al (2004) and Pleasence and Balmer (2012). Individuals also frequently reported their situation or the outcome of the dispute rather than their legal/rights and tended to also provide very vague responses which did not appear to have specific relevance to their particular dispute.…”
Section: Discussionmentioning
confidence: 86%
“…The CSJPS was the first legal needs survey worldwide to integrate (randomised) experimental research into its design, with this study one of a number included. Others included research on knowledge of marriage/cohabitation rights (Pleasence and Balmer, 2012), knowledge of consumer, employment and housing rights (Pleasence et al ., 2017) and the impact of different forms of between-wave engagement on response to longitudinal surveys (Cleary and Balmer, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, cohabitation can be represented as a matter of choice and freedom. However, several recent studies reveal a high level of public ignorance regarding the legal situation of cohabitants as distinct from certified spouses, and this obviously complicates understanding one as preferable over the other (Pleasence and Balmer 2012;Barlow et al 2005, 27-47). In any case, choices regarding cohabitation are limited freedoms.…”
Section: Degrees Of Separationmentioning
confidence: 97%
“…12. See Valverde (2006 on the "less than clear intentions" exhibited by some same-sex couples in North America; Pleasence and Balmer (2012) and Barlow et al (2005) on heterosexual ignorance as to the rights and obligations arising through cohabitation and marriage; Ellman and Braver (2012) on the gap between people's beliefs about how alimony should be decided and the legal facts; and, in a more personally reflective mode, Parsons (2008, 401). 13.…”
Section: Chaptermentioning
confidence: 97%